(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Nature and its elements are closely attached to human existence as the five elements that makes up the human body reflects the five elements that makes up all the matter that we see around us which has been one prime reason that herbal medicine has existed from time immemorial. Its prime principle is that deficiencies and defects in a five elemental body could always be repaired by drugs filled with abundance of same elements. Humans are also prone to a vast variety of diseases and health disorders as they tend to deviate from the things that keep the functional elements of the body in equilibirum and this leads to the onset of diseases. Such cases required medicines that can remove Dosha imbalance, promote and maintain the digestive fire, and at the same time act as a preventive measure for possible secondary diseases as well providing an immunomodulatory effect as well. Amritotharam kwatha is a renowned, widely accepted and therapeutically used Ayurvedic formulation by all Ayurvedic physicians throughout the country. The formulation is mentioned specifically in the text Sahasrayogam as well as other texts like Chikitsamanjari, Yogamritam in the contexts of Jwara chikitsa to combat Jwara of all types and its associated health issues. This article is intended to explore the pharmacological properties, actions and the therapeutic potential of Amritotharam Kwatha.